MECHANISMS AND SHARIA COMPLIANCE OF ZAKAT AL-FITR MANAGEMENT IN MOSQUES IN PONTIANAK CITY - Yusuf, Yusuf; Muhammad Ramdani (Jurnal Ikhtibar Nusantara, 2026)
This study analyzes the mechanisms and Sharia compliance in the management of zakat al-fitr by mosques in Pontianak City. Zakat al-fitr constitutes a crucial instrument for poverty alleviation and social justice; therefore, the effectiveness of its management by local amil (zakat administrators) at the mosque level is of significant importance. This research employs a qualitative juridical-empirical approach, collecting data on the processes of collection, recording, determination of beneficiaries (mustahik), and distribution across several major mosques. The findings indicate that, although the processes of collection and distribution are generally efficient, there are discrepancies in two main aspects: the formalization of amil status and compliance with the eight categories of recipients (asnaf) as stipulated in classical fiqh and contemporary legal frameworks, particularly Law No. 23 of 2011 on Zakat Management. Many mosques tend to distribute zakat exclusively to the poor and needy (fuqara’ and masakin) within their immediate communities, often neglecting other eligible categories or the formal requirement of ijab qabul (offer and acceptance). A juridical analysis based on the Shafi‘i school predominant in Indonesia reveals a normative gap, particularly concerning the practice of distributing zakat prior to the Eid al-Fitr prayer and the lack of comprehensive inclusion of all asnaf categories. This study underscores the necessity of standardized training and legal formalization for mosque-based amil. Such measures aim to ensure optimal benefits and full Sharia compliance, while strengthening the institutional role of mosques in promoting social welfare through proper zakat management.